Linkages between stomatal density and minor leaf vein density across different altitudes and growth forms - Zhang, Ming; Gao, Huirong; Chen, Shuang; Wang, Xiaochun; Mo, Weiyi; Yang, Xue; Wang, Xue; Wang, Zhibo; Wang, Ruili (Frontiers in Plant Science, 2022)
Water supply and demand in leaves are primarily determined by stomatal density (SD, water demand) and leaf vein density (VLA, water supply). Thus, covariation between them is essential for maintaining water balance. However, there is debate over whether these two traits vary in a coordinated way. Here, we gathered SD and minor VLA data from 224 species over four altitudinal gradients, and investigated their relationships across all species, growth forms, and different altitudes. Our findings demonstrated that SD and VLA were positively associated across all species, regardless of plant phylogeny. The positive relationships also occurred across different altitudes, although the strength became weak as the altitude increased. Moreover, the correlation of SD and VLA was found in shrubs and herbs, but their coordination occurred in trees only when the influence of the leaf area was removed. In addition, the stomatal number per minor vein length (SV) remained stable across different altitudes and growth forms. These findings suggested that coordinated variation between SD and VLA may be a general rule adopted by plants in the fluctuating environment, although caution must be exercised to draw this conclusion in woody plants with relatively large or small leaves.